Flow circulation dynamics in spur dike field enhanced by roughness elements - Muhammad Aqeel; Sohail Iqbal; Maaz Khan; Ghufran Ahmed Pasha; Usman Ghani; Afzal Ahmed; Xianrui Zhao (Ain Shams Engineering Journal)
Spur dike field (SDF) have recently gained attention as habitats for aquatic life. However, limited knowledge exists on how different configurations of roughness elements (RE) interact with recirculating flow in these environments. This study aims to investigate the influence of various RE arrangements (single, double, and triple layers) on hydrodynamics within SDF and at the nose of downstream spur dike, focusing on flow patterns and turbulence reduction. Numerical simulations using the CFD code FLUENT (ANSYS) were conducted to analyze flow intensity, turbulent kinetic energy, and circulation patterns. The findings show that REs significantly alters circulation dynamics, transforming a concentrated recirculation eye into multiple recirculation zones. The triple-layer configuration yielded the greatest reduction in velocity and turbulence up to 39% and 46% by reducing momentum exchange between SDF and the mainstream. This novel investigation of RE configurations provides insights into optimizing spur dike designs for improved hydraulic performance and ecological benefits.